2014
DOI: 10.1186/1471-2466-14-194
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive mechanical ventilation in patients with diffuse interstitial lung diseases

Abstract: BackgroundTo evaluate noninvasive ventilation (NIV) in diffuse interstitial lung diseases (DILD) patients with acute respiratory failure (ARF) according to baseline radiological patterns and the etiology of ARF.MethodsIn a multicenter, observational, retrospective study, consecutive DILD patients undergoing NIV because of an episode of ARF were evaluated in six Italian high dependency units. Three groups of patients were identified based on the etiology of ARF: those with pneumonia (Group A), those with acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 22 publications
(21 reference statements)
1
11
0
Order By: Relevance
“…Therefore, non‐invasive ventilation (NIV) is expected to be effective for acute and subacute IIP because of reductions in both endotracheal intubation and ventilator associated pneumonia. Although there are no randomized controlled studies to support the beneficial effect of NIV for acute/subacute IPs, several studies suggest its efficacy compared with the poor outcomes of patients with invasive mechanical ventilation in previous studies (Table ). It also was reported that early initiation of NIV and low severity of patient condition were associated with survival.…”
Section: Managementmentioning
confidence: 99%
“…Therefore, non‐invasive ventilation (NIV) is expected to be effective for acute and subacute IIP because of reductions in both endotracheal intubation and ventilator associated pneumonia. Although there are no randomized controlled studies to support the beneficial effect of NIV for acute/subacute IPs, several studies suggest its efficacy compared with the poor outcomes of patients with invasive mechanical ventilation in previous studies (Table ). It also was reported that early initiation of NIV and low severity of patient condition were associated with survival.…”
Section: Managementmentioning
confidence: 99%
“…Pulse steroids and immunosuppressive agents have been suggested for ILD exacerbations, particularly showing benefit in NSIP [85]. The use of glucocorticoids is controversial during septic shock states and may be beneficial in combination with mineralocorticoids [68]. Short term steroid use has been described to improve diuresis during heart failure exacerbations [86,87].…”
Section: Pharmacological Supportmentioning
confidence: 99%
“…NIV and HFNC are scarcely explored and should not delay intubation. NIV probably retains more risks than benefits [99], and P-SILI (see above) is possible also with HFNC.…”
Section: Modulation Of Drive: Ecco 2 Rmentioning
confidence: 99%